Los masajes y el desarrollo integral de los infantes de 0 a 12 meses de edad, año 2018. - Sánchez Sánchez, María Julia (2019)
The objective of this research is to determine the benefits of massages in the integral development of infants from 0 to 12 months of age; the type of research is bibliographic. Also identify the theoretical aspects of early childhood massages. On the other hand, characterize the development of infants from 0 to 12 months of age; in addition to theoretically relating the benefits of massage with language development, motor development, cognitive development, and development of infants. All this will serve to provide teachers with suggestions and recommendations on how to work with children at an early age to benefit their integral development. For the development of this research work methods were used as: Documentary registration, analysis, synthesis and paraphrasing of the information obtained, reaching the conclusion that the inclusion of massage in early care becomes the first and most important link of a chain that aims at the optimal evolution of the child that, together with its integral development within its sociocultural environment, provides the child with a series of experiences that will have a decisive influence on his or her future, gradually acquiring important functions at the motor, cognitive level , linguistic and social. That is why it is of great importance that specialist teachers know this research topic. Finally, a research work can be applied in institutions of initial level and by future researchers who are interested in the subject.